International Contribution to Nipah Virus Research 1999-2010 - H, Safahieh; S.A, Sanni; A.N, Zainab (Malaysian Journal of Library and Information Science, 2012)
This study examines 462 papers on Nipah virus research published from 1999 to 2010, identifying the active authors, institutions and citations received. Data was extracted from SCI-Expanded database, (Web of Science) and analyzed using descriptive figures and tables. The results show the growth of publication is incremental up to 2010 even though the average citations received is decreasing. The ratio of authors to articles is 1330: 426. The active contributing countries are USA (41.0%), Australia (19.3%), Malaysia (16.0%), England (6.5%) and France (5.6%). The productive authors are mainly affiliated to the Centre for Disease Control and Prevention, USA and Commonwealth Scientific and Industrial Research Organization (CSIRO) in Australia and University of Malaya Medical Centre, Malaysia. A total of 10572 citations were received and the ratio of articles to citation is 1: 24.8. Collaboration with the bigger laboratories in USA and Australia is contributive to the sustained growth of published literature and to access diverse expertise.